Climate-smart forage and feed actions: Exploring sustainable forage and feed practices for enhanced livestock nutrition, agricultural productivity, environmental health and climate resilience - Cramer, Laura K. (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
Ahead of SB62 in June 2025, the African Group of Negotiators Experts Support (AGNES) convened a pre-SB62 strategy meeting from 25th to 28th February 2025 to deliberate and prepare a common African position on the Global Goal on Adaptation, climate finance, gender, and agriculture. The session emphasised the urgency of strengthening implementation strategies, securing climate finance, and building cross-sectoral partnerships to advance effective and lasting climate action across the continent. This presentation, delivered by Dr Laura Cramer, gave an overview of climate-smart, AICCRA-validated technologies for integrated forage production, offering livestock farmers practical tools to adapt to a changing climate. The presentation covered a range of topics, including climate-smart livestock management, the importance of cultivated forage, forage integration into existing farm systems, forage production in degraded areas, benefits of fodder trees, livestock feed requirements and improved troughs, and smart seed bundles. The practical nature of the presentation was well received, underlining the value of accessible, scalable innovations in advancing Africa’s CSA agenda.